2020
DOI: 10.1088/1757-899x/988/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Effect of Fused Deposition Modelling Parameters for HIPS Material by Experimental Design and MRO Techniques

Abstract: Fused Deposition Modelling (FDM) is one of the popular AM technique which utilizes thin thermoplastic filaments to create prototypes and end use products. The parts processed through FDM method have poor mechanical properties and surface quality characteristics in comparison to conventional manufactured products. Extensive research is underway in various parts of the world to bring an enhancement in mechanical properties and other related characteristics of the parts produced through FDM for making the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…PETG has shown the maximum tensile strength than ABS material at 225°C extrusion temperature and 0.1 mm layer height. The experimental data obtained are trained using ANFIS and the results obtained are found to have a low error percentage (2.63%).Mohammed Raffic et al [22] applied the concepts of Taguchi orthogonal array, Grey relational analysis and TOPSIS to study the effect of FDM parameters such as slice height, infill density, shell thickness and raster angle for HIPS material and reported that the influencing parameter over flexural strength varies according to the method considered for evaluation. Ganesh Babu et al [23] exploited the benefits of experimental design and range analysis to optimize FDM parameters for materials such as PET-G, PLA and HIPS for enhancing fatigue strength and minimizing part weight.…”
Section: Introductionmentioning
confidence: 99%
“…PETG has shown the maximum tensile strength than ABS material at 225°C extrusion temperature and 0.1 mm layer height. The experimental data obtained are trained using ANFIS and the results obtained are found to have a low error percentage (2.63%).Mohammed Raffic et al [22] applied the concepts of Taguchi orthogonal array, Grey relational analysis and TOPSIS to study the effect of FDM parameters such as slice height, infill density, shell thickness and raster angle for HIPS material and reported that the influencing parameter over flexural strength varies according to the method considered for evaluation. Ganesh Babu et al [23] exploited the benefits of experimental design and range analysis to optimize FDM parameters for materials such as PET-G, PLA and HIPS for enhancing fatigue strength and minimizing part weight.…”
Section: Introductionmentioning
confidence: 99%